(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The relevance of this work is due to the following conditions, related to changes in the higher education system. As well as the growing needs of society for highly qualified specialists in engineering specialties. The use of a personality-oriented approach in foreign language lessons is one of the main problems in modern teaching. Great attention should be paid to the creation of an educational environment at the university in which the further socialization of the individual takes place and the professional-oriented skills of each student are developed. Each student is a person with their own needs and desires. The teacher should take into account all aspects of the personality-oriented approach when developing and implementing a foreign language course.